The relation of the number of hydrogen-bond acceptors with recoveries of immunosuppressants in DBS analysis. (August 2015) - Koster, Remco A; Alffenaar, Jan-Willem C; Botma, Rixt; Greijdanus, Ben; Uges, Donald RA; Kosterink, Jos GW; Touw, Daan J
Background: We investigated the influence of the number of hydrogen-bond acceptors on the recovery of immunosuppressant drugs and their structural analogs. This hypothesis was tested by evaluation of the extraction recoveries of tacrolimus, ascomycin, sirolimus, everolimus and temsirolimus with 12, 12, 13, 14 and 16 hydrogen-bond acceptors, respectively.Results: With an increasing number of hydrogen-bond acceptors of sirolimus, everolimus and temsirolimus, a decrease in recoveries was found while ascomycin showed recoveries corresponding to those of tacrolimus.Conclusion: This study showed that the number of hydrogen-bond acceptors of the analyte of interest may influence the recoveries in dried blood spot analysis and is a relevant factor to be investigated during method development and validation.